MENINGKATKAN KEMAMPUAN MOTORIK HALUS MELALUI BERMAIN PLASTISIN - Nining Witiyarni (JURNAL PENELITIAN DAN EVALUASI PENDIDIKAN, 2025)
This study aims to enhance the fine motor skills of Group B children at TK Sawunggaling Surabaya for the academic year 2018/2019 through the use of modeling clay as a learning medium. The research utilizes a Classroom Action Research (CAR) design, which involves direct intervention in the classroom setting to address specific educational challenges and improve teaching practices. The subjects of this study were 23 children, consisting of 11 boys and 12 girls. The research was conducted over three months, from August to October 2018, and was carried out in two cycles, each comprising planning, action, observation, and reflection phases. The results of Cycle I revealed that 61% of the children had achieved the minimum criteria for fine motor skills development. However, this percentage did not meet the predetermined success criteria of 75%-100%, indicating that 39% of the children had not yet reached the desired level of proficiency. Based on the reflection after Cycle I, modifications were made to the learning strategies, including more varied and interactive activities using modeling clay. In Cycle II, the overall success rate increased significantly to 78%, with 63% of children in the "Developing as Expected" category and 23% in the "Developing Very Well" category. These findings demonstrate that the revised strategies effectively stimulated children's engagement and motivation, leading to a notable improvement in their fine motor skills. The study concludes that using modeling clay as a learning medium is an effective strategy for developing fine motor skills in early childhood education. This approach not only fosters creativity and hand-eye coordination but also enhances children's readiness for further educational activities. Continuous reflection and evaluation in CAR have proven crucial in identifying barriers and optimizing teaching strategies to achieve better learning outcomes. Further research is recommended to explore the use of other play-based learning media that can support holistic development in early childhood education, considering a broader sample size and a longer study duration.